Effekt av myrsyra och beta-laktamas på penicillin- och S. aureus-halt i mjölk till kalvar - Raustein, Trine (2003)
A sample of milk inoculated with S. aureus was treated with penicillin, and Antipen (a new commercial product containing penicillinase) was added. To another sample with S. aureus and penicillin, formic acid to pH 5 was added, and to yet another sample, a combination of formic acid and Antipen was added. Controls with no penicillin were treated in the same way. All samples were cultured in room temperature. Bacterial culture on blood agar plates were done, and the samples were analysed to see whether penicillin remained. After 3 hours with Antipen, the penicillin was gone in all samples. S. aureus did not grow in the milk with penicillin only. In the milk with formic acid only, there was a slightly growth after 24 hours. In the milk with penicillin and formic acid, the bacteria grew to some extent, and in the samples with milk only, or with penicillin and Antipen, the bacterial growth was considerable. In the samples with penicillin, Antipen and formic acid, the same result as in the sample with formic acid only, was seen.